DETERMINASI LOYALITAS PEREMPUAN MILENIAL TERHADAP PEMBELIAN KOSMETIK HALAL - Jihan Nabila Zahara (Fakultas Ekonomi dan Bisnis, 2021)
This study aims to analyze the determination of millennial women's loyalty to the purchase of halal cosmetics. This study uses a quantitative survey approach by distributing questionnaires in the form of google form. The sampling technique used non-probability purposive sampling to collect data from a sample of 223 respondents with the criteria of millennial women born in the 1980s to 2000s, Indonesian citizens and had purchased halal cosmetics in the last 6 months. The analysis technique used in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS). Based on the results of the study, it shows that of the 5 hypotheses tested, all of them are accepted, namely religiosity has a significant effect on millennial women's loyalty in purchasing halal cosmetics (H1). Then, brand image (H2), profit value (H3) and halal certification (H4) have a significant and positive effect on consumer satisfaction. The high level of satisfaction also has a positive effect on the loyalty of millennial women in buying back halal cosmetic products and recommending them to others (H5). This discovery has significant implications that can help producers and distributors develop business strategies, especially halal cosmetic products.